Aquatic plants as phytoremediator for common carp fish (Cyprinus carpio) culture. Issue 1 (July 2020) - Taufik, I; Setijaningsih, L; Mulyasari,
Abstract: This research was conducted to optimize the performance of aquatic plants in maintaining water quality in common carp breeding. This study consisted of three treatments, namely: A. Lemna minor, B. Azolla pinnata, and C. Control (without plant) with three replications. The size of common carp juvenile used was ± 3 cm with a density of 150 individuals/m 2 . Feed was given ad satiation. The parameters observed were survival rate, weight, daily growth rate, water quality such as Biochemical Oxygen Demand (BOD), nitrogen and phosphate reduction. The research design used was Completely Randomized Design (CRD) with Analysis of Variance (ANOVA). Whereas the effectiveness of aquatic plants and water quality analyzed descriptively. The results showed that the highest survival rate and productivity of common carp breeding ponds were in treatment B, namely 86% and 463.80g. The growth rates between the three treatments were not significantly different (p> 0.05), each of which was 0.08; 0.08 and 0.09 g day −1 . The BOD reduction results in treatments A, B, and C, respectively 54.65, 54.65 and 52.33%. Nitrogen reduction in each treatment was (A) 67.54%; (B) 87.37%: (C) 25.27%. Furthermore, treatment A and B did not differ in the reduction of elemental P, respectively 52.68 and 55.20%, but in C the reduction was still low at 36.75%. Optimum water quality for dissolved oxygen in treatment A, B, and C respectively 7.24; 7.57 and 3.14 mg L −1 . The temperature range between treatments was 24.5 - 27.2 with a pH value of 6.00 - 6.87.